2015
DOI: 10.1103/physreva.92.063422
|View full text |Cite
|
Sign up to set email alerts
|

Dipole phase and photoelectron group delay in inner-shell photoionization

Abstract: We conduct a systematic study of the dipole phase and the photoelectron group delay (Wigner time delay) in inner shell photoionization of noble gas atoms from Ne to Xe. Our study encompasses the tender x-ray spectral range and extends to 1 keV photoelectron energy. We employ both the relativistic and non-relativistic versions of the random phase approximation with exchange. We identify the long range Coulomb and short range Hartree-Fock contributions to the dipole phase which governs the Wigner time delay vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…In this paper, we investigate both the angular and spin dependence of the time delay using the dipole relativistic random phase approximation (RRPA). We expand our previous relativistic studies of the time delay [8,9] and include the full interference of all the spin-orbit coupled photoionization channels. In the previous studies, only the time delay in the dominant channel was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we investigate both the angular and spin dependence of the time delay using the dipole relativistic random phase approximation (RRPA). We expand our previous relativistic studies of the time delay [8,9] and include the full interference of all the spin-orbit coupled photoionization channels. In the previous studies, only the time delay in the dominant channel was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with nonresonant time delays which are at the attosecond level. Thus, the time delays in the resonance region are about five orders of magnitude larger than nonresonant delays [10][11][12][13][16][17][18][19]; they are also considerably larger than the delays in the vicinity of a similar resonance in Ar [23].…”
Section: Resultsmentioning
confidence: 90%
“…An early review can be found in [9]. Later works are represented by [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Most of these investigations have involved nonresonant photoemission.…”
Section: Introductionmentioning
confidence: 99%
“…One needs a very sophisticated and advanced theoretical methodology to accurately probe the ultrafast electronic motion and study this subatomic world. With the impetus of two pioneering experimental investigations [2,3], photoionization time delay studies, as a means of investigating attosecond phenomena, have gained quite a bit of attention in recent years; a selection of some of this work can be found in [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. State-of-the-art experimental techniques have succeeded in probing the time domain in photoionization processes.…”
Section: Introductionmentioning
confidence: 99%